Penerapan Konsep Green Economy Dalam Pengembangan Wisata Berwawasan Lingkungan: Application of the Green Economy Concept in the Development of Environmentally Friendly Tourism - Yuli Herawati; Zaini Amin; Holidi Holidi; Bagus Dimas Setiawan (Media Ilmiah Teknik Lingkungan (MITL), 2023)
Green Economy is one of the global strategies related to social, economic and environmental aspects, in the aspect of tourism development it will affect management aspects, both in terms of economy, society, politics and culture. This research is a type of qualitative descriptive research using a phenomenology approach and a case study approach. This research aims to provide solutions and references in the application of the concept of green economy in the development of eco-friendly tourism. Implementation of green economy with the 3R concept (Reuse, Reuse, Recycle) which is carried out in the Banyu Langit Lake natural tourism, namely in the development of the tour planting various types of plantation crops that can be used for gardening and as a shelter, a fishing spot with a large pond, and empowering the social aspect, residents can open places to eat by providing ready-to-use huts and built several stalls for residents to sell on site, and a large parking area. It is hoped that green economy activities with the 3R concept (Reuse, Reuse, Recycle) can be an alternative in environmental preservation, especially tourism to improve the community's economy.